2018
DOI: 10.1155/2018/8485472
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Danhong Injection Combined with Naoxintong Capsule in Acute Coronary Syndrome Patients Undergoing PCI Operation: Study for a Randomized Controlled and Double‐Blind Trial

Abstract: Objective This double-blind and randomized placebo-controlled trial evaluated the safety and efficacy of Danhong injection combined with Naoxintong capsule in patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). Methods ACS patients scheduled to undergo PCI (n = 130) were equally and randomly apportioned to either a treatment or control group. After PCI, the treatment group received Danhong injection combined with Naoxintong capsule for 12 weeks, while the control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Z20026866). DHI is extracted from Salviae miltiorrhizae Radix and Carthami tinctorii Flos, and it can be used to treat CCVD [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Z20026866). DHI is extracted from Salviae miltiorrhizae Radix and Carthami tinctorii Flos, and it can be used to treat CCVD [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…NXT also can reduce the NO level and the expression of inducible nitric oxide synthase (iNOS) in the vessel wall to treat atheromatous (Zhong et al 2013). In clinics, NXT can be used for carotid atherosclerosis and cerebral infarction (Liang et al 2018), partly abrogate the impaired protective effect of high-density lipoprotein (HDL) on endothelial function (Lv et al 2016), and improve adverse cardiovascular events, atherosclerosis, and the expression of inflammatory factors in patients with acute coronary syndrome undergoing PCI, when combined with Danhong injection (Lv et al 2015;Zhao et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicated that DHI and NXTC have various pharmacological functions including improvement in endothelial action, anti-in ammatory, antioxidant properties, and antithrombotic effects [18][19][20][21][22]. Clinical studies found that DHI and NXTC can have the effects of regulating blood glucose, regulating blood lipids, antiplatelet, anticoagulation, improving heart function, improving endothelial function, improving symptoms, improving quality of life in patients with ACS [23][24]. However, due to the small sample size and unscienti c research methods, the conclusions are limited.…”
Section: Introductionmentioning
confidence: 99%